Urodynamic and neurophysiological evaluation in Parkinson's disease and multiple system atrophy. Issue 5 (May 1997) - Stocchi, F; Carbone, A; Inghilleri, M; Monge, A; Ruggieri, S; Berardelli, A; Manfredi, M
Abstract : AIMS: To determine whether Parkinson's disease and multiple system atrophy each has a distinct pattern of micturition abnormalities and whether a urodynamic evaluation could be useful in the differential diagnosis between the two diseases. METHODS: Sixty two patients (30 with Parkinson's disease and 32 with multiple system atrophy) underwent a complete urodynamic evaluation and neurophysiological testing. RESULTS: Of the parkinsonian patients 36.6% had normal micturition findings with normal bladder sensitivity; 26.7% had delayed or incomplete pelvic floor relaxation; 26.7% had hyperreflexia with vesicosphincteric synergy; and 10% had hyperreflexia with vesicosphincteric synergy associated with incomplete pelvic floor relaxation. Parkinsonian patients with a normal urodynamic pattern had significantly less severe disease and a shorter duration of disease in years than those who had abnormal patterns. Patients with hyperreflexia had significantly higher severity of disease. All the patients with multiple system atrophy had hyperreflexia with synergy. Two urodynamic patterns were identified: hyperreflexia with vesicosphincteric synergy (90.6% of patients), and hyperreflexia with vesicosphincteric synergy and incomplete pelvic floor relaxation (in 9.4%). Hyperreflexia with synergy correlated neither with the severity nor with the duration of disease. Sphincter EMG analysis showed that all the parkinsonian patients had normal sphincter EMG whereas 24 of the 32 patients with multiple system atrophy had neurogenic signs. CONCLUSIONS: Urodynamic evaluation and sphincter EMG are both useful tests in the differential diagnosis between Parkinson's disease and multiple system atrophy. Urodynamic findings may be abnormal before patients with multiple system atrophy reach an advanced stage of the disease. Recordings of EMGs from perineal muscles become abnormal as the disease progresses in multiple system atrophy but not in Parkinson's disease.